PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA PERBUATAN MELAWAN HUKUM AKIBAT MENDIRIKAN BANGUNAN DIATAS TANAH PUSAKA TINGGI (ANALISIS PUTUSAN NOMOR 1/PDT. G/ 2021/ PN.SOLOK) - Viana, Wira Okta; Vitrah, Ipan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
As a binding agent in the sale and purchase of land, in principle it is the same as an agreement in general which is subject to the conditions for the validity of an agreement as contained in Article 1320 of the Civil Code. Apart from that, Article 1338 Paragraph 3 of the Civil Code states that the implementation of the agreement must be carried out in good faith. When one of the parties does not carry out the contents of the agreement as they should, that is where a dispute occurs which is an unlawful act, which sometimes ends in a judge's decision and a trial process in court. Based on the background above, the problem can be formulated as follows: First, what is the judge's consideration in deciding cases of unlawful acts resulting from erecting buildings on high heritage land in Decision Number 1/Pdt. G/ 2021/ PN.Solok. Second, what are the legal consequences in deciding cases of unlawful acts resulting from building buildings on high heritage land in decision Number.1/Pdt.G/2021/PN.Solok. In this research, the research specifications are descriptive. The approach method used in this research is a normative juridical approach, namely analyzing the judge's considerations in deciding cases of unlawful acts resulting from building buildings on high heritage land in Decision Number 1/Pdt.G/2021/PN.Solok. The data source used is secondary data. Based on the results of the research and discussion, it can be concluded as follows: First, in decision Number.1/Pdt.G/2021/PN.Solok, the judge gave juridical considerations regarding the elements in Article 1365 of the Civil Code. Apart from that, consideration of the evidentiary strength of documentary evidence, witnesses, and statements from the Plaintiff and Defendant. The parties to the case acted in good faith during the trial, the Plaintiff and Defendant agreed to state that the object of the dispute was high inheritance, and the Defendant admitted and regretted his actions in building a foundation on the land of the object of the case without the permission of the Plaintiff. Second, the legal consequences in deciding cases of unlawful acts resulting from building buildings on land in decision Number.1/PDT.G/2021/PN. Solok, namely the judge, granted the plaintiff's demands, if the decision was inkracht then the contents of the judge's decision were executed in order to restore the plaintiff's rights.Keywords: Judge's considerations, unlawful acts, high inheritance land.